DIRECTIONS AND MEANS OF ACTIVATING THE INTEGRATED INNOVATIVE DEVELOPMENT OF THE ENTERPRISE - BAS, Ihor (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article focuses on issues of ensuring business viability and development in critically difficult conditions of instability. It is shown that an important factor in ensuring the strengthening of competitive positions and the creation of prerequisites for sustainable management and further progress of domestic enterprises is their innovative activity and activity. Therefore, the purpose of the article is to substantiate the directions and means of activation of the integrated innovative development of domestic enterprise. It was concluded that the integrated innovative development should be understood as a systematic approach, according to which the enterprise plans and implements all types of innovations, implements basic functions in the field of innovative development, and also forms and develops its own internal system of management of innovative and technological development. The directions of the enterprise’s integrated innovative progress have been identified. A set of means of activating the processes of integrated innovative growth of business entities has been developed. It was established that in order to ensure the integrated innovative development of the enterprise, its top management should implement a set of measures aimed at achieving such target tasks as the spread of innovations in all functional areas of business, uniform and full-fledged innovative development in all target market segments, systematic combination and application of all types and types of innovations, formation of an interconnected integrated system of internal-external communications in the field of R&D, vertical diversification of innovative development processes. The measures that should be implemented for this purpose are the following: application of a centralized and multi-level approach (delegation of tasks of planning, organization and implementation of innovative activities to the level of structural subdivisions of the enterprise); equal attention to DiR, creation and implementation of innovations that apply to all groups of product support and each of the target market segments of the company’s product positioning on the market, sufficient attention to product, technical, technological, marketing, management, etc. innovations through the division of tasks in the field of innovative development by types of innovations; establishment and development of the company’s digital internal and external communications system in the field of R&D, cooperation in the generation of ideas, creation and implementation of innovative solutions; "engagement" on the basis of cooperation of consumers, suppliers, etc. counterparties of the enterprise in order to generate ideas and satisfy the interests of all participants of such a system.